Journal of mammology. - American Society of Mammalogists (Oxford : Oxford University Press, 1919)
The Journal of Mammalogy has been the flagship publication of the American Society of Mammalogists since 1919 and was voted one of the top 100 most influential serials in biology and medicine of the 20th century. This highly respected international scientific journal is produced 6 times per year and promotes interest in mammals throughout the world by the publication of original and timely research on all aspects of the biology of mammals.
"Published on behalf of American Society of Mammalogists"--Home page.
Description based on online resource; title from home page (viewed on October 3, 2016).
Keywords: Mammals -- Periodicals